Wolbachia Horizontal Transmission Events in Ants: What Do We Know and What Can We Learn? - Tolley, Sarah J. A.; Nonacs, Peter; Sapountzis, Panagiotis (Frontiers in Microbiology, 2019)
While strict vertical transmission insures the durability of intracellular symbioses, phylogenetic incongruences between hosts and endosymbionts suggest horizontal transmission must also occur. These horizontal acquisitions can have important implications for the biology of the host. Wolbachia is one of the most ecologically successful prokaryotes in arthropods, infecting an estimated 50-70% of all insect species. Much of this success is likely due to the fact that, in arthropods, Wolbachia is notorious for manipulating host reproduction to favor transmission through the female germline. However, its natural potential for horizontal transmission remains poorly understood. Here we evaluate the fundamental prerequisites for successful horizontal transfer, including necessary environmental conditions, genetic potential of bacterial strains, and means of mediating transfers. Furthermore, we revisit the relatedness of Wolbachia strains infecting the Panamanian leaf-cutting ant, Acromyrmex echinatior, and its inquiline social parasite, Acromyrmex insinuator, and compare our results to a study published 15 years ago by Van Borm et al. (2003). The results of this pilot study prompt us to reevaluate previous notions that obligate social parasitism reliably facilitates horizontal transfer and suggest that not all Wolbachia strains associated with ants have the same genetic potential for horizontal transmission.